MANAGEMENT OF VILLAGE PRIVATE ENTERPRISES AS AN ACCOMPLISHMENT OF THE INDEPENDENCE ECONOMIC VILLAGE - Kholmi, Masiyah; Jati, Ahmad Waluya; Suhardi, Diding (Jurnal Ekonomi Pembangunan, 2018)
This research aims to describe the governance of Village-Owned Business Entities in Megaluh, Jombang. Data collection with questionnaires and documents. This research method using quantitative-descriptive. The results show that BUMDES in Megaluh was implemented with the purposes of BUMDES and increase the economics of the village. But there are several limitations in the governance of BUMDES, which is the educational background of the management of BUMDES governance was occupied by high school or vocational school graduates (56,1%), the majority of BUMDES characteristics are in the form of savings and loans (56,4%), trade (29,6%), rental (6,3%), and else (7,7%). BUMDES does afford to contribute to village cash or PADes of the still low (2,39%).